Inhibition of Notch1 Signaling Alleviates Endotoxin-Induced Inflammation Through Modulating Retinal Microglia Polarization - Cheng, Zhixing; Yang, Yao; Duan, Fang; Lou, Bingsheng; Zeng, Jieting; Huang, Yanqiao; Luo, Yan; Lin, Xiaofeng (Frontiers in Immunology, 2019)
Microglial cells are resident immune cells and play an important role in various cerebral and retinal inflammatory diseases. Notch1 signaling is involved in the microglia polarization and the control of cerebral inflammatory reactions. However, its role in endotoxin-induced uveitis (EIU) remains unknown. This study aimed to investigate the role of Notch1 signaling on retinal microglia polarization and inflammation in the cultured retinal microglial cells and EIU rat model. We found that Notch1 signaling blockade with N-[N-(3, 5-difluorophenacetyl)-1-alany1-S-phenygly -cine t-butyl ester (DAPT) shifted retinal microglia phenotype from pro-inflammatory M1 phenotype (COX2+ and iNOS+) to anti-inflammatory M2 phenotype (Arg-1+) and reduced the release of pro-inflammatory cytokines both in vivo and in vitro. Moreover, DAPT treatment contributed to prevent retinal ganglion cells from apoptosis, reduce the intraocular infiltrating cells, and attenuate the impairment of retinal function. Taken together, these results suggest that inhibition of Notch1 signaling could alleviate the inflammatory response in EIU rat mainly through regulating the polarization of retinal microglia. Therefore, Notch1 signaling might be a promising therapeutic target in the treatment of ocular inflammatory diseases.